The current issues on financial technology (Fintech) in personal financial planning - Ab Rahman, Siti Maziah; Shaari, Rustam; Yasin, Ahmad Bukhari; Wan Muhammad, Wan Firdaus; Mat Rusok, Nur Hazelen (Journal of Islamic, Social, Economics and Development, 2025)
Fintech innovations are transforming personal financial planning, offering unprecedented convenience and efficiency; however, several challenges and considerations arise with this evolution. This abstract explores the current issues in fintech applications for personal finance, focusing on key areas such as data security, over-reliance on automation, and regulatory compliance. While AI-driven tools and robo-advisors enhance budgeting and investment management1, the risk of data breaches and identity theft poses a significant threat to users. Over-reliance on automated tools can also lead to blind spots in financial management, potentially causing users to miss creeping subscription charges or dwindling savings. Moreover, the rapid pace of fintech innovation often outpaces the development of regulatory frameworks, creating uncertainty and compliance challenges for both startups and established players. This abstract highlights the need for a balanced approach that leverages the benefits of fintech while addressing its associated risks to ensure consumer protection, financial stability, and ethical practices. This study is to understand the significance of Fintech, we employed a comprehensive research methodology such as literature review, data analysis and others. In this report we were able to tell the importance and purpose of fintech in our life and economy. This report also contains the issues that we have found within the current technology of fintech throughout the world. To combat the issues, we have provided the best ways to negate the issue with recommendations on how to improve on fintech. In conclusion, our group assignment emphasizes Fintech's significant influence on contemporary financial systems and finding the issues that are present with the current advancement of fintech.